Acceleration Strategies for Competitiveness: Integrating Green Entrepreneurship Practices, Local Content Optimization, and Empowered Entrepreneurial Capacity - Junedi, Junedi; Ida Abdul Gopar (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This research aims to examine strategies for accelerating competitiveness through integrating environmentally-based entrepreneurial practices, optimizing local content utilization, and strengthening competitive entrepreneurial capacity. The underlying problem is the low level of competitiveness, driven by limited poverty principles, a lack of local love and potential, and weak entrepreneurial capacity among business actors. This research employs a quantitative approach with a survey method complemented by an ethnographic perspective. Data were obtained through observation, questionnaire distribution, interviews, and a literature review of SME’s in the Cikarang, Bekasi area, using purposive sampling as the basis for selecting respondents. Data analysis was conducted using linear regression. The results reveal that green entrepreneurship, optimizing local content, and empowered entrepreneurial capacity have a positive and significant influence on increasing SME’s competitiveness. Therefore, this study confirms that integrating these three variables is a strategic and sustainable strategy for accelerating the strengthening of SME’s competitiveness.